Impact on parasitemia, survival time and pro-inflammatory immune response in mice infected with Plasmodium berghei treated with Eleutherine plicata - Antônio Rafael Quadros Gomes; Antônio Rafael Quadros Gomes; Ana Laura Gadelha Castro; Ana Laura Gadelha Castro; Gleison Gonçalves Ferreira; Heliton Patrick Cordovil Brígido; Everton Luiz Pompeu Varela; Everton Luiz Pompeu Varela; Valdicley Vieira Vale; Liliane Almeida Carneiro; Maria Fâni Dolabela; Maria Fâni Dolabela; et al. (Frontiers in Pharmacology)
In vitro studies with Plasmodium falciparum have demonstrated the antiparasitic activity of E. plicata, attributed to its naphthoquinones. This study reports on pro-inflammatory changes in mice infected with P. berghei and correlates these changes with parasitemia and survival. The ethanol extract of Eleutherine plicata (EEEp) was fractionated under reflux to obtain the dichloromethane fraction (FDMEp) and isolated compounds from E. plicata, relating these to survival time and parasitemia. Antimalarial activity was evaluated using the Peters suppressive test, with mice infected with Plasmodium berghei and treated with E. plicata, assessing parasitemia and survival over 30 days. The pro-inflammatory profile was determined by measuring interleukin-10, interferon-γ (IFN-γ), and nitric oxide levels. EEEp, FDMEp, and eleutherol showed activity on the 5th day of infection, with only FDMEp being active on the 8th day. Treatment with EEEp and FDMEp extended animal survival, reduced IFN-γ and NO levels, and increased IL-10 levels. Eleutherol significantly altered the response, with eleutherol glucuronide seemingly active by binding to lactate dehydrogenase, inhibiting hemozoin metabolism, leading to parasite death. Pro-inflammatory changes did not appear to correlate with survival and reduced parasitemia. In summary, FDMEp and eleutherol reduced parasitemia, extended survival, and modulated the inflammatory response. FDMEp and eleutherol are promising candidates for developing new antimalarial drugs.